Kontekstualisasi Nilai-Nilai Maqashid Syariah Jaseer Auda dalam Piagam Madinah terhadap Kehidupan Bernegara (Studi di Kota Metro Lampung) - Fidian Abron (CV. Creative Tugu Pena, 2024)
The birth of the Medina Charter after the Prophet Muhammad SAW moved to Yathrib/Medina. The Prophet together with all the people of Medina created a cultural foundation, building harmony in religious, economic, social and political life. The researcher discusses the Maqoshid Syariah values ​​from Jaseer Auda's perspective in the Medina Charter. The aim of this research is to analyze the Maqoshid Syariah values ​​from Jaseer Auda's perspective in the Medina Charter. The type of research used is a case study, which is a type of research that explores a problem with detailed boundaries, with in-depth data collection, and includes various sources of information. This research is limited by time and place. Data analysis in this research was carried out during and after data collection and analysis (interpretation), the aim of which was to sharpen the focus of observations and deepen questions related to the topic under study. Data analysis after data collection is a continuation of the previous analysis, where data is presented systematically and confirms propositions, hypotheses, concepts or models built based on field data. In the Indonesian context, the Medina Charter offers a model of democracy developed by the Prophet which emphasizes equality, fairness, justice and civility. This research also shows that the values ​​of Jasser Auda's Maqashid Syariah in the Medina Charter are very relevant in dealing with various socio-political problems in Metro Lampung City. These values ​​include harmony, justice and civility which are applied in various aspects of life, including religious and state life. Therefore, the Medina Charter can be used as a reference in developing more inclusive and sustainable policies. Keywords: Maqashid Syariah Values, Jaseer Auda's Maqashid Syariah